Activities of the Association of the Ladies of Charity of St. Vincent de Paul in Kraków during World War I - Włodyka, Aleksandra (Wydawnictwo Uniwersytetu Rzeszowskiego, 2023)
Associations of the Ladies of Charity of St Vincent de Paul were established in the Polish lands in the 1850s. One of the first association was founded in Kraków. The aim of this article is to present the activities of the Ladies of Charity and the Steward Maids [Panny Ekonomki] in the years before and during World War I. The members of the association provided the sick poor with emergency care such as making bandages or providing food and other daily necessities. In addition to material assistance, great emphasis was also placed on the religious aspect of the wards’ lives. From the beginning of the 20th century, the Steward Maids concentrated on their work in the infirmary and, during the war, on organising nursing courses.

Stowarzyszenia Pań Miłosierdzia św. Wincentego a Paulo powstawały na ziemiach polskich od lat 50. XIX w. Jedno z pierwszych utworzono w Krakowie. Artykuł ma na celu przybliżyć działalność pań miłosierdzia oraz panien ekonomek w latach poprzedzających I wojnę światową oraz w jej trakcie. Członkinie stowarzyszenia udzielały ubogim chorym doraźnej pomocy, takiej jak wykonywanie opatrunków czy dostarczanie żywności i innych artykułów codziennego użytku. Poza pomocą materialną duży nacisk kładziono również na religijny aspekt życia podopiecznych. Panny ekonomki od początku XX w. skupiały się na pracy w ambulatorium, a w czasie wojny na organizowaniu kursów pielęgniarskich.
Działalność Stowarzyszenia Pań Miłosierdzia św. Wincentego a Paulo w Krakowie w latach I wojny światowej
Keywords: association; Kraków; charity; religiosity; women; stowarzyszenie; dobroczynność; religijność; kobiety